1991
DOI: 10.1152/ajpheart.1991.261.2.h292
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of dynamic AV nodal properties and application to predict rate-dependent AV conduction

Abstract: A number of functional properties of the atrioventricular (AV) node have been described in response to changes in the atrial input rate. The purpose of this study was 1) to develop quantitative descriptors of these properties, and 2) to determine whether they can account for rate-dependent changes in AV nodal conduction. The delay in AV nodal conduction of single premature beats (recovery) was found to be an exponential function of coupling interval with a time constant of 66 +/- 2 (+/- SE) ms. A single abbrev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…While ERPN increases with basic rates (14,16,70), FRPN shortens (13,14,16,20,25,51), so that the significance of these changes remains confounding. The dependence of A 2 H 2 on the preceding cycle length is similarly expressed at all BCL (41,54,66). However, a short BCL (Fig.…”
Section: Av Nodal Function As Assessed With S 1 S 2 Protocolsmentioning
confidence: 75%
See 3 more Smart Citations
“…While ERPN increases with basic rates (14,16,70), FRPN shortens (13,14,16,20,25,51), so that the significance of these changes remains confounding. The dependence of A 2 H 2 on the preceding cycle length is similarly expressed at all BCL (41,54,66). However, a short BCL (Fig.…”
Section: Av Nodal Function As Assessed With S 1 S 2 Protocolsmentioning
confidence: 75%
“…For instance, these properties account for transient responses to linear ramp increase and decrease in cycle length inducing hysteresis in AV nodal conduction time (12,75). These properties also quantitatively account for a variety of other rate-induced AV nodal responses including Wenckebach cycles (54,62,68,74). A recent study also provides analytical and modeling data supporting their involvement in human supraventricular tachyarrhythmias (46).…”
Section: Physiology and Assessment Of Transient Av Nodal Responsesmentioning
confidence: 91%
See 2 more Smart Citations
“…[12][13][14][15][16][17][18][19][20][21][22] Microelectrode recording studies have shown that the proximal, rather than distal, AV node plays a critical role in the generation of facilitation. 23,24 Based on our previous study 11 that Cx40-deficient mice display impaired AV nodal conduction, we hypothesize that Cx40-deficient mice display altered patterns of AV nodal facilitation compared with wild-type controls.…”
Section: Introductionmentioning
confidence: 99%